PENGGUNAAN TEKNIK ASSOSIASI BEBAS DAN PLAY THERAPY DALAM KONSELING KELOMPOK UNTUK MEMBANTU MENGENTASKAN MASALAH SISWA PADA KELAS X 1 DI SMAN TEGALOMBO - ASNA TOVIYANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This Classroom Action Research aims to help solve student problems through group counseling services using free association methods and play therapy. The research subjects were class X1 SMAN Tegalombo. Where the data analysis technique uses a qualitative approach (Milles and Huberman) which includes data collection, data reduction, data exposure, triangulation, and drawing conclusions. The results of the study can be summarized as follows: 1. The free association technique helps make it easier for students to uncover problems, problems that were successfully collected by the counselor through the free association technique, namely, fear of not going to class, being scolded by parents, afraid of teachers, not doing assignments, not being able to concentration and compassed friends. 2. Through play therapy activities students become happy, familiar, not awkward. 3. Implementation of group counseling in cycle I there are still students who are less communicative, and there are students who have carried out counseling decisions but the problem is not resolved, there are those who have not carried out counseling decisions and there are those who carry out counseling decisions where problems are resolved but new problems arise, so that in group counseling cycle II the counselor mediates with the party causing the problem and uses the